2019
DOI: 10.2308/tar-2017-0284
|View full text |Cite
|
Sign up to set email alerts
|

Are Investors Warned by Disclosure of Conflicts of Interest? The Moderating Effect of Investment Horizon

Abstract: Financial analysts are required to disclose conflicts of interest (COI) in their research reports, but there is limited evidence on the effectiveness of COI disclosures. We investigate whether the influence of disclosing COI in analyst reports on investors' decision making depends on investment horizon. Experimental results show that short-term investors who view a COI disclosure are significantly less willing to invest in the recommended stock compared to short-term investors who do not view such a disclosure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 96 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…We observe this pattern irrespective of whether the analyst who issues an aggressive price target also issues an aggressive earnings estimate (Experiment 1) or a nonaggressive earnings estimate (Experiment 2). Overall, we contribute to the literature on investors' judgments of financial analysts (Brav and Lehavy 2003;Shanthikumar 2007, 2014;Kelly et al 2012;Liu et al 2020). We show that when investors evaluate multiple analysts' price targets with other related information in the form of earnings estimates, by evaluating jointly rather than separately, investors are less susceptible to the influence of aggressive analysts.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…We observe this pattern irrespective of whether the analyst who issues an aggressive price target also issues an aggressive earnings estimate (Experiment 1) or a nonaggressive earnings estimate (Experiment 2). Overall, we contribute to the literature on investors' judgments of financial analysts (Brav and Lehavy 2003;Shanthikumar 2007, 2014;Kelly et al 2012;Liu et al 2020). We show that when investors evaluate multiple analysts' price targets with other related information in the form of earnings estimates, by evaluating jointly rather than separately, investors are less susceptible to the influence of aggressive analysts.…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, experimental research has also provided evidence that investors react to information provided by financial analysts (Hirst et al 1995;Kelly et al 2012;W. Chen and Tan 2013;Winchel 2015;Liu et al 2020).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…16 Collectively, our participants share similar investment knowledge and work experiences with participants representative of non-professional investors that Rennekamp (2012) and Liu et al (2020) recruited from MTurk (an online participant sourcing platform similar to Prolific) for their respective studies.…”
Section: Discussionmentioning
confidence: 99%
“…Kempf et al (2017) found that when shareholders are distracted (offer less than ideal monitoring), earning management becomes more challenging to detect due to the temporarily lower monitoring caused by investor distraction. If this is the case, managers would have more leeway to manipulate accruals and fundamental operations to inflate reported earnings (Chen et al , 2020; Liu et al , 2020). All accessible stock information cannot adequately inform retail investors due to the expense of both looking for and processing the information (Ying et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%